Polyvinylpyridine–carbon dots composite-based novel humidity sensor - Khouloud Jlassi (2583832) (2023)
This work describes the rational design of thin films based on PVP-modified carbon dots for potential resistive humidity sensing application, prepared via spin coating on ITO substrates. The modified carbon dots were manufactured from graphite waste and modified with PVP to test the synergetic effect of the two materials. The surface hydrophilicity, morphology, and sensing properties were studied. AFM has been performed to investigate the prepared films’ texture and distribution over the surface. Overall, the hydrophilicity of the prepared films increases with concentration, leading to enhanced water vapor absorption on the surface of the sensing film. As a result, the sensor’s sensitivity is improved with the increasing concentration of PVP–CDs. The electrical response of the PVP–CDs composite film sensor shows a higher sensitivity level above 80% RH sensor with an irregular response; however, the concentration of 0.5 wt%, higher sensitivity, and linear change in impedance response was noted compared to other concentrations. Other Information Published in: Applied Physics A License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00339-023-06908-3